Peran Pemerintah Desa Dalam Melestarikan Budaya Pesta Panen Di Desa Long Telenjau Kecamatan Peso Hilir Kabupaten Bulungan - Wempi Feber; Iskandar Iskandar (Journal of Innovation Research and Knowledge, 2026)
It is a major concern for village governments that preserving and promoting cultural heritage is a shared responsibility of both the government and the community in safeguarding local traditions and wisdom. Therefore, this study focuses on examining the role of the village government in preserving the harvest festival tradition in Long Telenjau Village, Peso Hilir District, Bulungan Regency, as well as identifying the forms of activities that can be undertaken to ensure the continuity of this cultural tradition. This study employed a qualitative research approach. The qualitative method was used to provide an in-depth, detailed, and comprehensive description of the empirical realities underlying the phenomenon. Data were collected from both primary and secondary sources, with interviews serving as the primary data collection technique. As previously described, the study was conducted using a qualitative approach. The findings reveal that the Long Telenjau Village Government plays a significant role in preserving the harvest festival tradition by providing financial support, facilities, and event promotion. Furthermore, the village government actively encourages community participation in celebrating the harvest festival. The preservation efforts include community empowerment, economic empowerment, and socio-cultural empowerment. These initiatives have proven to be effective, as evidenced by the high level of community enthusiasm and participation in the implementation of the harvest festival